Improving Delivery Outcomes with the Application of Murottal Therapy Al-Qur'an on Length of Second Stage of Labor and Apgar Score. - Rosmiarti; Tukimin; Khairunnisa Humairoh (Jurnal Inspirasi Kesehatan, 2023)
Introduction: The second stage of labor is called the expulsion period, starting when the opening of the cervix is complete (10 cm) and ending with the birth of the baby with his force and straining the fetus is pushed out until birth. Childbirth is a stress response that the body responds to. Anxiety in pregnant women is caused by psychosocial factors such as the need for security and comfort. Al-Qur'an stimulants can generate delta waves of 63.11% with reduced anxiety in the mother making the muscles more relaxed and the mother can go through labor easily so there are no cases of prolonged labor and can improve the welfare of the fetus. Method: This type of research is a quasi-experimental study that aims to determine the increase in labor outcomes by applying the Murottal Al-Quran to the Length of the Second Stage of Labor and the APGAR Score. While the research design used was a pre- experimental design with a posttest only with a control group design to measure the effect of murottal QS. Ar-Rahman in the experimental group by comparing it with the control group. The population in this study were all mothers giving birth during the first active phase at the Ar-Rahmah Indaralaya Maternity Clinic in Palembang. Results: There were 66 respondents (55.5%) who applied Murottal Al-Quran with a duration of 2 under 1 hour, while 53 respondents (44.5%) did not apply Murottal Al-Quran with a duration of 2 under 1 hour. Respondents who applied Murottal Al-Quran in the absence of asphyxia were 64 people (66%) while respondents who did not apply Murottal Al-Quran in the absence of perineal rupture were 33 people (34%). Discussion: There was a difference in the length of stage II between the intervention group and the control group after the application of Murottal Al- Qur'an and there were differences in APGAR scores between the intervention group and the control group after the application of Murottal Al-Qur'an.